2015
DOI: 10.1007/s13204-015-0410-1
|View full text |Cite
|
Sign up to set email alerts
|

On the application of NiO nanoparticles to mitigate in situ asphaltene deposition in carbonate porous matrix

Abstract: Prevention of asphaltene formation in reservoir rocks can result in resolving a severe long-lasting issue in petroleum production. The present research addresses the issue in the context of exploring the potential effect of nickel oxide (NiO) nanoparticles in destabilizing asphaltene deposition in porous media, in the presence of carbon dioxide. To ensure proper distribution within the system and to retain future field-scale applicability, the NiO nanoparticles were exposed to the in situ oil via injection gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…One of the effective methods for controlling asphaltene deposition is to use chemical additives such as surfactants [3,4], polymeric inhibitor [5] and adsorbents [6]. Up to now, several adsorbents were used for asphaltene adsorption from oil solution such as mineral surfaces (kaolin, calcite and dolomite) [6], clay and reservoir rocks [7,8], metal surfaces (stainless steel and gold) [9,10] and several kinds of metal and metal oxide nanoparticles (MgO, TiO 2 , NiO, CaO, Fe 3 O 4 , Al 2 O 3 , etc) [11][12][13][14][15][16][17][18]. The reasons of interest on using nanoparticles in recent years for asphaltene adsorption are the special properties of nanoparticles such as their high surface area to volume ratio, functionalizable surface and their smaller size that cause easier transportation in porous media and enhance the performance of fluid flow and oil recovery [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the effective methods for controlling asphaltene deposition is to use chemical additives such as surfactants [3,4], polymeric inhibitor [5] and adsorbents [6]. Up to now, several adsorbents were used for asphaltene adsorption from oil solution such as mineral surfaces (kaolin, calcite and dolomite) [6], clay and reservoir rocks [7,8], metal surfaces (stainless steel and gold) [9,10] and several kinds of metal and metal oxide nanoparticles (MgO, TiO 2 , NiO, CaO, Fe 3 O 4 , Al 2 O 3 , etc) [11][12][13][14][15][16][17][18]. The reasons of interest on using nanoparticles in recent years for asphaltene adsorption are the special properties of nanoparticles such as their high surface area to volume ratio, functionalizable surface and their smaller size that cause easier transportation in porous media and enhance the performance of fluid flow and oil recovery [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies showed that the nanoparticles are good choices for adsorption and catalytic oxidation of asphaltene in crude oil upgrading process [11,13,19] while, limited researches have been carried out on using nanoparticles in porous media for asphaltene adsorption and consequently reduction of asphaltene deposition through oil flooding [17,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, as proven by the studies above, once asphaltene compounds are adsorbed on the reservoir rock surface, wettability is altered to an oil-wet state until an effective treatment for asphaltene desorption is applied. Recently, nanoparticles have shown high potential for in-situ applications in the areas of inhibition of different types of formation damage (Franco, Nassar, Ruiz, Pereira-Almao, & Cortés, 2013c;Hashemi et al, 2015;Kazemzadeh, Malayeri, Riazi, & Parsaei, 2015a;Nassar, Betancur, Acevedo, Franco, & Cortés, 2015a;Shayan and Mirzayi, 2015;Zabala et al, 2014), enhanced oil recovery (Ehtesabi, Ahadian, & Taghikhani, 2014;Giraldo, Benjumea, Lopera, Cortés, & Ruiz, 2013a;Hashemi, Nassar, & Almao, 2014a;Hashemi, Nassar, & Pereira-Almao, 2012;Hashemi, Nassar, & Pereira Almao, 2013a;Hosseinpour, Mortazavi, Bahramian, Khodatars, & Khodadadi, 2014;Karimi et al, 2012;Kazemzadeh et al, 2015b) and heavy and extra-heavy oil upgrading (Franco et al, 2013b;Franco et al, 2014;Franco et al, 2015;Hamedi Shokrlu and Babadagli, 2013;Hosseinpour, Khodadadi, Bahramian, & Mortazavi, 2013;Hashemi, Nassar, & Pereira Almao, 2013b;Hashemi, Nassar, & Pereira Almao, 2014b;Mora, Franco, & Cortés, 2013;Nassar et al, 2015b;Nassar et al, 2012). Regarding the asphaltene-related problems, nanoparticles can restore wettability from an oil-wet state to a waterwet state (Giraldo et al, 2013a;Karimi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, nanoparticles have a high surface area to volume ratio, functionalizable surface, high adsorption capacity, and increased mobility due to their small size . Recently, many researchers have investigated the adsorption of asphaltenes on the surface of metal oxide nanoparticles. However, most studies have focused on the adsorption of asphaltenes by nanoparticles inside porous media. The efficacy of nanoparticles in reducing or inhibiting asphaltene deposits inside the production tubing has not been fully explored. Having the nanoparticles in the bulk phase will create a competition between the surface of nanoparticles and the production tubing surface in attracting asphaltenes.…”
Section: Introductionmentioning
confidence: 99%